Genetic polymorphisms and the development of invasive bacterial infections in children. (March 2016) - Esposito, Susanna; Bosis, Samantha; Orenti, Annalisa; Spena, Silvia; Montinaro, Valentina; Bianchini, Sonia; Zampiero, Alberto; Principi, Nicola
To evaluate the associations between single nucleotide polymorphisms (SNPs) of factors involved in the development of invasive bacterial disease (IBD) in children, 47 SNPs of 18 candidate genes were analysed in 49 children with IBD and 100 controls. The G/T genotype of TLR2 rs2149356 and the C genotype of LTA rs2229094 were associated with significantly reduced risk of developing IBD ( P = 0.04 and P = 0.05, respectively), whereas the C/T genotype of RFP175 rs1585110 was associated with a significantly higher risk of developing IBD ( P = 0.02). These results support the evidence that some genetic variants of factors involved in innate immunity may influence IBD risk in children.